Faktor-Faktor Perilaku Anak SD Yang Dapat Menyebabkan Penyakit Cacing Nematoda Usus Di SDN 6 Arga Makmur Kabupaten Bengkulu Utara - Dwi Hermawati; Pipit Verawatie (Jurnal Vokasi Kesehatan, 2022)
The purpose of the study was to determine the relationship between the use of footwear, washing hands before eating, using the latrine with the incidence of intestinal nematode worm disease. The research method used by the researcher in this research is an analytical survey with a cross sectional approach to see the relationship between behavioral factors in elementary school children and the incidence of intestinal nematode worm disease. The research population was 205 people with the number of samples used as many as 135 respondents. The results showed that the independent variables, namely: the use of footwear, washing hands before eating and using the latrine, were significantly related to the dependent variable, namely the incidence of intestinal nematode worm disease. With p<0.05 (p=0), the value of x²=29,883 was obtained for the factor of wearing footwear against the incidence of worm disease, the behavior of washing hands before eating obtained a value of x² = 21,656 (p=0), and the use of latrines with a value of x² = 6.638 ( p=0.05).